2015
DOI: 10.1002/uog.13407
|View full text |Cite
|
Sign up to set email alerts
|

Cervical length in late second and third trimesters: a mixture model for predicting delivery

Abstract: Objectives To examine the distribution of cervical length (CL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Amongst women who delivered preterm, a significant proportion belonged to the short‐cervix group and this was more prominent the earlier the PTD occurred. Similarly, we have described previously a mixture model for third‐trimester CL (24–40 weeks) in which a quarter of the population formed the short‐cervix group in which the majority (89%) of PTD arose. These findings suggest that, in the second, as well as in the third trimester, there is a considerable proportion of women with a short cervix, containing a significant fraction of PTD.…”
Section: Discussionsupporting
confidence: 78%
“…Amongst women who delivered preterm, a significant proportion belonged to the short‐cervix group and this was more prominent the earlier the PTD occurred. Similarly, we have described previously a mixture model for third‐trimester CL (24–40 weeks) in which a quarter of the population formed the short‐cervix group in which the majority (89%) of PTD arose. These findings suggest that, in the second, as well as in the third trimester, there is a considerable proportion of women with a short cervix, containing a significant fraction of PTD.…”
Section: Discussionsupporting
confidence: 78%
“…The association of short CL with early delivery has mainly been studied in the second trimester but there is emerging evidence suggesting that early assessment in the first trimester may identify women at risk for PTB, albeit with lower detection rates . Additionally, in line with the original observation of Iams et al , we have lately shown that the third‐trimester CL measurement is more sensitive than the second‐trimester measurement in predicting PTB . Yet thus far, studies on third‐trimester CL use it mainly as a predictor of the time of delivery .…”
Section: Introductionsupporting
confidence: 70%
“…Overall, first‐trimester CL seems to predict late miscarriage, second‐trimester cervical assessment performs well for very early PTB and late third‐trimester CL measurement is better for identifying late prematurity . The appropriate longitudinal chart is crucial in a sequential approach because it enables the quantification of CL change.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that late second- and third-trimester CL is useful in the estimation of the probability for SPD [20]. The present study provides evidence on the value of CL measurement after 24 weeks for the prediction of SPD, suggesting that there is place for a repeat examination of the cervix in the early third trimester.…”
Section: Discussionsupporting
confidence: 50%